2023
DOI: 10.1186/s40560-023-00682-3
|View full text |Cite
|
Sign up to set email alerts
|

The Restrictive Red Blood Cell Transfusion Strategy for Critically Injured Patients (RESTRIC) trial: a cluster-randomized, crossover, non-inferiority multicenter trial of restrictive transfusion in trauma

Abstract: Background The efficacies of fresh frozen plasma and coagulation factor transfusion have been widely evaluated in trauma-induced coagulopathy management during the acute post-injury phase. However, the efficacy of red blood cell transfusion has not been adequately investigated in patients with severe trauma, and the optimal hemoglobin target level during the acute post-injury and resuscitation phases remains unclear. Therefore, this study aimed to examine whether a restrictive transfusion strat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
4
0
1

Year Published

2024
2024
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 32 publications
(41 reference statements)
1
4
0
1
Order By: Relevance
“…This was a post hoc analysis of the RESTRIC trial, a cluster-randomized, crossover, non-inferiority multicenter trial that was conducted across 22 institutions in Japan and involved 422 patients [ 7 ]. The design of the RESTRIC trial has been previously published [ 12 ].…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…This was a post hoc analysis of the RESTRIC trial, a cluster-randomized, crossover, non-inferiority multicenter trial that was conducted across 22 institutions in Japan and involved 422 patients [ 7 ]. The design of the RESTRIC trial has been previously published [ 12 ].…”
Section: Methodsmentioning
confidence: 99%
“…To address this gap, the Restrictive Transfusion Strategy for Critically Injured Patients (RESTRIC) trial was conducted to assess the non-inferiority of a restrictive red blood cell (RBC) transfusion strategy (hemoglobin level of 7 to 9 g/dL) compared to a liberal RBC transfusion strategy (hemoglobin level of 10 to 12 g/dL) in patients experiencing potential or ongoing massive hemorrhage after trauma during the acute phase of injury [ 7 ]. The trial showed that the two groups had similar 28-day survival rates and incidences of any type of adverse event.…”
Section: Introductionmentioning
confidence: 99%
“…In recent years, there has been increasing recognition that more restrictive transfusion thresholds may be not only safe but also beneficial in specific clinical situations. 11 , 12 , 13 , 14 , 15 , 16 , 17 …”
Section: Anemia Tolerancementioning
confidence: 99%
“…ben (wobei der Hb nicht alleiniger Transfusionstrigger sein soll)[1,2]. Durch die RESTRIC-Studie wurde auch für das Trauma kein signifikanter Nachteil unter diesem restriktiven Transfusionsziel nachgewiesen[6].Eine Normothermie wird empfohlen[1,2].…”
unclassified